Heavy Metal and Nutrient Loading of River Rwizi by Effluents from Mbarara Municipality, Western Uganda - Egor, Moses; Mbabazi, Jolocam; Ntale, Muhammad (International Journal of Chemistry and Materials Research, 2014)
This study, carried out in the wet annual April seasons during the period 2010-2011, was geared towards the quantification of heavy metal and nutrient levels in the surface water of River Rwizi, the main Mbarara municipal drainage system. The effect of Mbarara municipal effluents on heavy metal and nutrient (phosphate, nitrite, nitrate and ammonium) loading of River Rwizi was investigated along with the changes in some basic water quality parameters, i.e., pH, conductivity and hardness. The filtered water samples were digested with a perchloric acid/nitric acid/hydrochloric acid mixture. Total heavy metals Cu, Zn, Cd and Pb were determined by flame atomic absorption spectrophotometry. Nutrients were determined by standard Wagtech methods. The results showed that there was a significant difference in concentration of lead (p = 0.047) and zinc (p = 0.018) between 2010 and 2011, with average concentrations being higher downstream. The concentrations of lead and cadmium were much higher than the WHO guideline values in drinking water (0.01 μg ml-1 and 0.003 μg ml-1, respectively). There was no significant difference in concentration of cadmium in 2010 along River Rwizi around Mbarara Township (p = 0.180). Nutrient loading in the domestic water source also indicated a gradual annual increase - hence a call for early pollution control measures by the relevant authorities.